Marker Genes of Clear Cell Renal Cell Carcinoma - Dolomatov, Sergey; Zukow, Walery (Journal of Education, Health and Sport, 2024)
An analysis was conducted on marker genes indicating the induction of clear cell renal cell carcinoma (ccRCC) and their role in the pathogenesis of this oncological disease. The diagnostic and therapeutic approaches for ccRCC are evolving with the identification of marker genes. The use of molecular biology methods has enabled the detection of somatic mutations in RCC marker genes like VHL, BAP1, OGG1, FLCN, MDM2, TP53, and RNF139. Targeted drugs like sorafenib, sunitinib, bevacizumab, pazopanib, axitinib, everolimus, and temsirolimus are being utilized in the treatment of RCC metastases. The diagnostic value of specific alleles in marker genes like rs1642742 and rs779805 of the VHL gene, rs1052133 of the OGG1 gene, rs2279744 of the MDM2 gene, and rs1597368777 of the TP53 gene has been confirmed in detecting ccRCC. Mutations in these marker genes play a significant role in the pathogenesis of ccRCC and are associated with the development and progression of the disease. The identification of these mutations can aid in the diagnosis, prognosis, and treatment of ccRCC. Marker genes are essential in understanding the molecular mechanisms underlying ccRCC. Mutations in genes like VHL, BAP1, OGG1, FLCN, MDM2, TP53, and RNF139 are key drivers of ccRCC pathogenesis. The diagnostic and therapeutic implications of these mutations are significant in the management of ccRCC. Further research into the role of marker genes in ccRCC is essential for developing targeted therapies and improving patient outcomes.